1995
DOI: 10.1007/978-1-4612-0823-5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Nonlinear Dynamics

Abstract: Mathematics Subject Classifications (1991): 39xx, 92Bxx, 35xx Library of Congress Cataloging-in-Publication Data Kaplan, Daniel, 1959-Understanding nonlinear dynamics I Daniel Kaplan and Leon Glass. p. cm. -(Texts in applied mathematics; 19) Includes bibliographica1 references and index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
265
0
5

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 525 publications
(270 citation statements)
references
References 0 publications
0
265
0
5
Order By: Relevance
“…It can be shown that not all states of the system are equally stable (equally probable to occur) but that some network states, as dictated by the GRN, represent stable steady states, the attractor states, to which the similar ("nearby") states that are not stable will be "attracted" (2). Thus, GRNs exhibit multistability (coexistence of multiple attractors) (3). Stochastic fluctuations caused by molecular noise in gene expression (4)(5)(6) can allow the network to "jump" from attractor to attractor-hence, the latter is actually metastable.…”
mentioning
confidence: 99%
“…It can be shown that not all states of the system are equally stable (equally probable to occur) but that some network states, as dictated by the GRN, represent stable steady states, the attractor states, to which the similar ("nearby") states that are not stable will be "attracted" (2). Thus, GRNs exhibit multistability (coexistence of multiple attractors) (3). Stochastic fluctuations caused by molecular noise in gene expression (4)(5)(6) can allow the network to "jump" from attractor to attractor-hence, the latter is actually metastable.…”
mentioning
confidence: 99%
“…the number of active degrees of freedom or invariants, such as the maximal Lyapunov exponent, of a particular system solely by analysing the time course of one of its variables. Thus, the theory of nonlinear time series analysis offers tools that bridge the gap between experimentally observed irregular behaviour and deterministic chaos theory [19][20][21][22]. Although, in this sense, the transition between deterministic chaos theory and the analysis of irregular experimental traces appears smooth, the reality is very different.…”
Section: Introductionmentioning
confidence: 99%
“…Fractal-based techniques are global methods that have been successfully applied to estimate the attractor dimension of the underlying dynamic system generating time series [44]. Unless other global methods, they can provide as ID estimation a non-integer value.…”
Section: Fractal-based Methodsmentioning
confidence: 99%